2019
DOI: 10.35916/thmr.v1i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dayak (Eleutherine palmifollia (L) Merr) Extracts Against Escherichia coli In Vitro

Abstract: Dayak onion (Eleutherine palmifolia (L.) Merr) is hereditary used by the Indonesian Kalimantan Dayak community as a medicinal plant with antimicrobial activity. The active ingredient of Dayak onions can inhibit the growth of bacteria such as Escherichia coli. The purpose of this study was to determine the effectiveness of Dayak extract (Eleutherine palmifollia (L) Merr) in inhibiting the growth of Escherichia coli in vitro. This research method is experimental. Posttest Only Control Group Design research desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Meanwhile, a mild inhibitory activity was recorded against S. aureus and P. aeruginosa with MIC values of 25 µg/mL as compared to the positive control, chlarithromycin. Similarly, a research performed by Mahmudah et al [42] indicated that the water extract of the E. palmifolia bulb inhibited the growth of E. coli significantly, with an inhibition diameter of 6 mm at the lowest concentration of 10% and 30 mm at the highest concentration of 100% as compared to the positive control, ceftriaxone (35 mm).…”
Section: Anti-bacterial Propertiesmentioning
confidence: 80%
“…Meanwhile, a mild inhibitory activity was recorded against S. aureus and P. aeruginosa with MIC values of 25 µg/mL as compared to the positive control, chlarithromycin. Similarly, a research performed by Mahmudah et al [42] indicated that the water extract of the E. palmifolia bulb inhibited the growth of E. coli significantly, with an inhibition diameter of 6 mm at the lowest concentration of 10% and 30 mm at the highest concentration of 100% as compared to the positive control, ceftriaxone (35 mm).…”
Section: Anti-bacterial Propertiesmentioning
confidence: 80%
“…Indications of the content of Eleutherine Americana Merr extricates from hytochemical screening results containing: flavonoids, saponins, tannins, triterpenoids, alkaloids, anthraquinones, naphthoquinones, and steroids [16,17]. Dayak onions have been displayed to have antioxidant [18,19], antifungal [20] antimitotic [21] and antiacne [22].…”
Section: Introductionmentioning
confidence: 99%
“…Eleutherine palmifolia (L.) Merr is empirically used to treat infectious diseases. It has been scientifically proven active against Pseudomonas fluorescens (Fransira, Yanuhar and Maftuch, 2019), Shigella dysenteriae (Wicaksono, Runadi and Firmansyah, 2018), and Escherichia coli (Mahmudah, Muntaha and Muhlisisn, 2019). E. palmifolia contains alkaloids, glycosides, flavonoids, phenolics, steroids, and tannins (Harlita, Oedjijono and Asnani, 2018;Mutiah et al, 2019;Limantara et al, 2020).…”
Section: Introductionmentioning
confidence: 99%